2018
DOI: 10.1021/acs.jpclett.8b02741
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Investigation of the Chromophore Structure of Heliorhodopsins

Abstract: Heliorhodopsins (HeRs) are a new category of retinal-bound proteins recently discovered through functional metagenomics analysis that exhibit obvious differences from type-1 microbial rhodopsins. We conducted the first detailed structural characterization of the retinal chromophore in HeRs using resonance Raman spectroscopy. The observed spectra clearly show that the Schiff base of the chromophore is protonated and forms a strong hydrogen bond to a species other than a water molecule, highly likely a counteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 41 publications
7
56
0
Order By: Relevance
“…This could be observed as well in the case of HeR-48C12 and the absence of ion transport activity for both BcHeR and HeR-48C12 may indicate that the heliorhodopsin family has other functions such as a light-sensor or the light-induced transport of molecules such as glycopeptides or amphiphilic molecules as proposed in previous studies. 18,27,34 We next characterized the absorption spectra and retinal configuration of purified BcHeR in dark-and in light-illuminated conditions. Many microbial rhodopsins and even HeR-48C12 present not only a light-adapted state 18 but also a dark-adapted state.…”
Section: Resultsmentioning
confidence: 99%
“…This could be observed as well in the case of HeR-48C12 and the absence of ion transport activity for both BcHeR and HeR-48C12 may indicate that the heliorhodopsin family has other functions such as a light-sensor or the light-induced transport of molecules such as glycopeptides or amphiphilic molecules as proposed in previous studies. 18,27,34 We next characterized the absorption spectra and retinal configuration of purified BcHeR in dark-and in light-illuminated conditions. Many microbial rhodopsins and even HeR-48C12 present not only a light-adapted state 18 but also a dark-adapted state.…”
Section: Resultsmentioning
confidence: 99%
“…Rhodopsins commonly have seven TMs and the retinal chromophore. Recently, a distinct and abundant group of microbial rhodopsins, HeRs, has been discovered [37][38][39] . Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises seven TMs with the retinal chromophore, as in the other rhodopsins [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Rhodopsins commonly have 7 TMs and the retinal chromophore. Recently, a distinct and abundant group of microbial rhodopsins, the heliorhodopsins (HeRs) has been discovered [36][37][38] . Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises 7…”
Section: Discussionmentioning
confidence: 99%
“…This study deepens our knowledge about the structures and functions of enzyme rhodopsins, and will facilitate the design of a dark activity-reduced Rh-PDE for optogenetic applications.Rhodopsins commonly have 7 TMs and the retinal chromophore. Recently, a distinct and abundant group of microbial rhodopsins, the heliorhodopsins (HeRs) has been discovered [36][37][38] . Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises 7TMs with the retinal chromophore, as in the other rhodopsins [39][40][41] .…”
mentioning
confidence: 99%